La importancia de los factores internos y externos en el éxito empresarial; The importance of internal and external factors in business success - Paz Rico Belda; Bernardí Cabrer-Borrás (Revista de Métodos Cuantitativos para la Economía y la Empresa, 2021)
– Increasing the productivity of an economy requires improvements in the productivity of its companies, and therefore greater business success. It should be noted that a company on the road to success is more productive. The objective of this paper is to analyse how internal and external factors influence the labour productivity of companies. This paper provides evidence that recognises the importance of the quality of business management, on the one hand, and the factors related to the functioning of markets and institutions, on the other, in determining the productivity of companies. The results show that business management practices and the quality of the business environment jointly determine the productivity of companies. However, there are differences according to the size of the companies, so that smaller companies have lower business productivity that can be increased if they improve their management practices and their physical capital endowment per worker. In addition, if institutions invest in improving the environment in which businesses operate, they are more likely to achieve greater business success.
Keywords: C13; D22; L22; M10; 330; business success; labour productivity; management practices; institutional quality